Role of ICT for Managing Diversity of Mathematics Classes: Experiences of Teachers (The Educator Journal, 2024)
Diversity issue in the present context is a global issue of socialization. It has not yet been materialized into the education system in Nepal. The education system of a country should prepare students to function in today’s diverse society. There are issues emerging in the effectiveness of the diversity management and the concerns how to better shape the diverse classroom in Nepal. This paper focuses on issues such as teacher’s experiences in diverse classes, classroom management, and role of ICT integrated pedagogy to manage diverse classroom context. It also discusses the context, and experiences of teachers that can bring the diverse classroom situation into the right track. For this purpose, I apply narrative inquiry of two mathematics teachers (one male and one female) of University campus Kirtipur with more than ten years’ of teaching experience. In depth interview related to the experiences of teachers managing diverse in higher mathematics classes were conducted and found that there are different types of diversity in the context of Nepalese mathematics classroom viz. cognitive diversity and social diversity. However, the management of diversity is a great job for teachers, the use of ICT tools plays vital role in this direction. Although, teachers are little familiar to the diversity management skill they try to manage such type of diversity by supporting their students personally through ICT tools. Diversity works with social constructivist approach in educational field is trying to discuss in this paper. It also presents the role of ICT integrated pedagogy to manage the diverse classes by respecting student’s personal feelings.